Rules of Jurisdiction of the Regulation Brussels I bis – Application of General Jurisdiction Rule and Special Jurisdiction Rule under Close Connecting Factor (Article 7 (1)) – Lithuanian Perspective - Pranevičienė, Kristina; Gaubienė, Neringa (Teisė, 2024)
This paper focuses on the application of the general jurisdiction rule and the special jurisdiction rule under Article 7 (1) of Regulation (EU) No. 1215/2012 of the European Parliament and of the Council of 12 December, 2012, on jurisdiction and the recognition and enforcement of judgments in civil and commercial matters (recast) (Regulation Brussels I bis) in Lithuanian jurisprudence. It firstly briefly presents the general jurisdiction rule, and then penetrates into the discussion about the special jurisdiction rule under Article 7 (1) of Regulation Brussels I (recast) revealing the jurisprudence of the Court of Justice of the European Union (CJEU) and answering the question whether Lithuanian courts apply this legal norm correctly. By analysing the Case Law, the authors reveal the peculiarities of the national Case Law and disclose how it is compatible with the jurisprudence of the CJEU. The research aims to contribute to the development of the Lithuanian legal doctrine, by analysing Regulation Brussels I bis.
Keywords: jurisdiction; civil and commercial disputes; Regulation Brussels I (recast); Regulation No. 1215/2012; Regulation Brussels I bis